History repeats itself: consumption of a local traditional roast pork meat recipe leads to Salmonella ser. Give cases in Greece - Georgia Mandilara; Anthi Chrysostomou; Michalis Polemis; Daiana Duro; Grigorios Karaj; Eleni Mathioudaki; Kleon Karadimas; Kyriaki Tryfinopoulou; Kassiani Mellou; Theologia Sideroglou (James Cook University, 2024)
Introduction: An outbreak of gastroenteritis due to Salmonella Give, a very rarely identified serotype in human isolates in Greece, occurred in participants of a religious festival in a rural area of southern Greece, in September 2022. The objectives of this study were to describe the outbreak in terms of epidemiology, identify the vehicle of transmission of the foodborne pathogen and recommend prevention measures. Methods: The outbreak was linked to the consumption of a local traditional recipe of roasted pork meat served by a street food vendor. In 2018, the same food item, served in a restaurant in the same region, was implicated in another S. Give outbreak. Results: Outbreak investigations revealed that outbreak-associated isolates, of food and human origin, belonged to the same S. Give strain. Significant deficiencies regarding food safety practices were identified. Conclusion: Technical knowledge about pathogen transmission paths is important in order for both food handlers and consumers to follow hygiene and sanitary measures, mainly in cases of mass gatherings, where large quantities of food are prepared, handled, cooked and served. Efficient official supervision, mainly during summer festivals, is required in order to avoid recurrence of foodborne infections by different combinations of pathogens/food commodities.